2021
DOI: 10.1080/21870764.2021.1896094
|View full text |Cite
|
Sign up to set email alerts
|

­Effect of sintering treatment time on the sintering behaviour and thermal shock resistance of Li2O-Al2O3-SiO2 glass-ceramics

Abstract: In order to determine the correlation of flexural strength and thermal shock resistance properties, the sintering behavior of Li 2 O-Al 2 O 3 -SiO 2 (LAS) glass-ceramics at different sintering treatment times and the effect of thermal shock cycles on LAS glass-ceramics were investigated. The LAS glass-ceramics were isothermally treated at 1100°C from 1.5 to 4.5 h. Phase transformation of major crystalline of β-spodumene and minor crystalline of ZrTiO 4 revealed unchanged as sintering treatment time increased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…24 For the samples sintered at 1300 • C, the grain continued to grow to produce boundary stress, leading to the expansion of pores and a slight decrease in the degree of densification. 25 As can be seen from Figure 6B, at the same temperature, the bulk density of the samples increased with the increase of the spodumene content. At different sintering temperatures, the bulk density of the samples was found to first increase and then decrease.…”
Section: Densification Analysismentioning
confidence: 72%
See 3 more Smart Citations
“…24 For the samples sintered at 1300 • C, the grain continued to grow to produce boundary stress, leading to the expansion of pores and a slight decrease in the degree of densification. 25 As can be seen from Figure 6B, at the same temperature, the bulk density of the samples increased with the increase of the spodumene content. At different sintering temperatures, the bulk density of the samples was found to first increase and then decrease.…”
Section: Densification Analysismentioning
confidence: 72%
“…In the middle and later stages of sintering, the grain growth led to the formation of pores, and the samples reached their densest state 24 . For the samples sintered at 1300°C, the grain continued to grow to produce boundary stress, leading to the expansion of pores and a slight decrease in the degree of densification 25 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34][35] Chen et al 36 studied the effect of Li 2 O content in LAS glass on the crystal phase and CTE and found β-quartz solid solution-based crystal phases precipitation in glass-ceramics, and CTE in 30-300 • C range decrease with Li 2 O content increase. Lutpi et al 37 investigated the relationship between thermal treatment duration and thermal shock behavior of LAS glass, confirmed that the extension of thermal durations resulted in the growth of nanocrystals, from 0.55 to 0.67 μm, and induced microhardness increase, from 3.90 to 5.47 GPa. Keyvani et al 38 found that Al 2 O 3 contents in LAS glass had critical effect on crystallization processes and the microstructure of glass-ceramics by SiO 2 consumption.…”
Section: Introductionmentioning
confidence: 93%